The extent of the environmental tax contribution to achieving sustainable development - Sattar Ahmed, Sanaa (Opción, 2019)
Environmental tax is one of the important tools in achieving sustainable de- velopment. This type of tax appeared in the early twentieth century, and these taxes aim to reduce the percentage of pollutants by imposing them on polluter. It has motivational effects for modifying behavior in proportion to the require- ments of preserving the environment. The researcher has used the analytical method according to the data issued by the Central Agency for Statistics on the volume of waste in Diyala Governorate, the most important conclusions reached by the researcher is that the environmental tax can reduce pollution when imposing financial sums on individuals causing pollutants, and thus we will achieve sustainable development.